2014
DOI: 10.1002/chem.201403382
|View full text |Cite
|
Sign up to set email alerts
|

Alkenyl/Thiol‐Derived Metal–Organic Frameworks (MOFs) by Means of Postsynthetic Modification for Effective Mercury Adsorption

Abstract: The synthesis of new functionally diverse alkenyl-derived Cr-MIL-101s (MIL=material of Institute Lavoisier) was realized by a novel and convenient postsynthetic modification (PSM) protocol by means of the carbon-carbon bond-forming Mizoroki-Heck reaction. The new PSM protocol demonstrates a broad scope of substrates with excellent tolerance of functionality under mild reaction conditions. Moreover, a new metal-organic framework (MOF) that bears both alkenyl and thiol side chains prepared by means of the tandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 78 publications
(15 reference statements)
0
37
0
Order By: Relevance
“…Obviously, the appearance of the silver signal at binding energies of 368.2 eV and 374.2 eV corresponding to the peaks of Ag 3d 5/2 and Ag 3d 3/2 , respectively, suggests that silver(I) has been loaded in the sample [29]. [19][20][21][22]. MOFs containing chelation ligands, such as 2,2'-bipyridine, can also afford metal ions, whereas the main issue however is the limitation of the choice of appropriate ligands [23][24][25][26].…”
Section: Characterization Of Mofsmentioning
confidence: 97%
See 1 more Smart Citation
“…Obviously, the appearance of the silver signal at binding energies of 368.2 eV and 374.2 eV corresponding to the peaks of Ag 3d 5/2 and Ag 3d 3/2 , respectively, suggests that silver(I) has been loaded in the sample [29]. [19][20][21][22]. MOFs containing chelation ligands, such as 2,2'-bipyridine, can also afford metal ions, whereas the main issue however is the limitation of the choice of appropriate ligands [23][24][25][26].…”
Section: Characterization Of Mofsmentioning
confidence: 97%
“…It is postulated that if specific metal ions can be incorporated into the framework successfully, the adsorption performance for iodide will be enhanced greatly. Up to now, metal ions have been encapsulated into MOFs using various chelating methods, for example, postsynthetic method (PSM) [19][20][21][22] or in situ synthesis [23][24][25][26]. However, these methods reported may face the obstacles of relatively complex process or limitation of choice of appropriate ligands.…”
Section: Page 3 Of 23mentioning
confidence: 98%
“…19 Others have shown that post-synthetic modification allows thiol groups to be added to a pre-made MOF: in the case of MIL-101(Cr) this allowed formation of an Hg 2+ adsorbent. 20 In this paper we explore the possibility of producing a thiol-modified MIL-53, and use, for the first time, sulfur K-edge XANES spectroscopy to prove successful incorporation of a thiolated ligand into a MOF. To our knowledge the only previous attempt to add thiol groups to MIL-53 used post-synthetic reaction of amino-modified MIL-53 with mercaptoacetic acid.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Most of these thrilling properties of MOFs,which are related to their porous character and rich host-guest chemistry, [24] can be tuned by an appropriate functionalization of the channels.T aking advantage of the methods provided by coordination chemistry,a na ccurate design effort [25] should thus lead to water-stable [26,27] MOFs for use as "mercury receptors". [28][29][30][31][32][33] Nature has evolved mechanisms to effectively distinguish one metal from another.H ow metal ions move to and from their target destinations in the active site of ametalloenzyme, or as structural components of other biomolecules such as nucleic acids,e fficiently contributes to the regulation of biological processes.A ni nteresting example within this context is the mercury reductase (MR), [34] ar edox enzyme that catalyzes the reduction of highly toxic Hg 2+ into more benign Hg 0 .T he active center of this enzyme represents as ource of inspiration for coordination chemists working in the area of mercury detoxification, and efforts trying to mimic it have been pursued. [34] MOFs could thus also find application as vessels encapsulating biological systems.…”
mentioning
confidence: 99%